Research on the factors influencing the identity of Chinese doctor of education candidates - Liangliang Hu; Jiawei Chen; Mengxue Li; Shasha Zhang; Wenlan Zhang; Zhaoyang Liu (Scientific Reports)
Abstract Doctor of Education (Ed.D) candidates are facing an identity crisis, and enhancing their identity has become an urgent issue. This study applies grounded theory methodology, targeting 32 Ed.D candidates from a university in China. Data were collected through semi-structured focus groups and one-on-one interviews, and analyzed using Nvivo11, following open, axial, and selective coding processes. The study found that cognitive tendency, doctoral motivation, emotional experience, and professional identity are the subjective factors influencing Ed.D candidates’ identity. Learning environment, training model, relationship network, and development opportunity are the objective factors. Based on these findings, the study analyzed the deep-seated relationships between influencing factors and identity, establishing a model of influencing factors. Finally, targeted and systematic strategies to enhance the identity of Ed.D candidates were proposed based on the research conclusions.